Clinical outcome of breast cancer patients with N3a (>= 10 positive lymph nodes) disease: has it changed over years? - DANE, FAYSAL; KAYA, HANDAN; GÜLLÜOĞLU, MAHMUT BAHADIR; YUMUK, PERRAN FULDEN (HUMANA PRESS INC, 2011)
It has been shown that breast cancer patients with N3a (10 positive lymph nodes) had a poor prognosis. We planned to investigate the clinical outcome BC patients who presented with N3a disease and had no evidence of systemic metastasis at the time of diagnosis. We made a retrospective chart review of breast cancer patients who had a parts per thousand yen10 positive lymph nodes and received adjuvant systemic therapy in Marmara University Hospital between 1998 and 2008. We recorded clinical, pathologic and treatment characteristics of the patients and analyzed the survival outcome. We identified 73 patients with N3a disease who were treated in Marmara University Hospital between 1998 and 2008. The median age was 52. Most (75%) of the patients had invasive ductal histology, 75% had T2/T3 tumors, 36% had grade 3 tumors. The median number of metastatic lymph nodes was 15. Estrogen and progesterone receptors were both positive in 61% and both negative in 16+ tumors. Her-2/neu status was assessed in 68% of the tumors; 18% of patients had 3+ and 50% had negative scores. Six patients had triple negative tumors. All patients except one received adjuvant chemotherapy and radiotherapy. Seventy-four percent of patients received anthracycline/taxane-based chemotherapy. Fifty-nine patients received adjuvant endocrine therapy, 42% them received aromatase inhibitors. Five of the 13 Her-2 positive patients received adjuvant trastuzumab. With a median follow-up of 47 months, 5-year disease and overall survival rates were 66 and 81%, respectively. Twenty-four patients had relapsed and 14 patients died. Her-2 status and the number of lymph nodes (< 20 vs. a parts per thousand yen20) had significant impact on disease-free survival in the univariate analysis (P = 0.03 and 0.05, respectively) and Her-2 retained its significant impact on disease-free survival in the multivariate analysis (P = 0.05). The prognosis of BC patients with N3a disease has changed favorably in the past decade with the current standards of care.
Keywords: Breast cancer; Node positive; N3a disease; HIGH-DOSE CHEMOTHERAPY; STEM-CELL SUPPORT; ADJUVANT CHEMOTHERAPY; RANDOMIZED-TRIAL; SURVIVAL; THERAPY; METAANALYSIS; DOXORUBICIN; MANAGEMENT; WOMEN